Successful Pulmonary Rehabilitation in COPD During COVID-19 Pandemic Era: A Case Report - Widjanantie, Siti Chandra; Ayuningtyas, Putu Duhita; Susanto, Agus Dwi (Jurnal Respirologi Indonesia, 2024)
Background: Chronic obstructive pulmonary disease (COPD) patients are at high risk for COVID-19 infection and severe pulmonary complications. Exercise-based pulmonary rehabilitation (PR) in outpatient settings is essential for COVID-19 survivors with COPD comorbidities, providing the most critical patient benefits, but it is challenging during the pandemic.Case: A sixty-four-year-old man with COPD since 2 years ago, a history of COVID-19 one month ago, and Pulmonary Tuberculosis since 1 year ago presented with chief complaints of tiredness, cough, and breathlessness after walking for more than 100 meters. We performed PR, including breathing retraining exercise, chest mobility exercise, active cycle breathing technique (ACBT), posture correction, and aerobic exercise with static ergo-cycle for 8 weeks.Discussion: After 8 weeks of PR, there was a 3% increase in the O2 saturation level from 94-95% room air to 98%, an increase of single breath counting test (SBCT) from 20 to 38 counts, improvement of peak cough flow from 100-110-100 to 420-435-425 L/minute, and peak flow meter from 140-150-145 to 380-400-400 L/minute. Before PR the patient could not perform the sit-to-stand test (STS) and a 6-minute walking test (6MWT), but after 8 weeks of PR, STS was 5 times in 30 seconds, and 6MWT maximum distance was 248 meters. COPD assessment test (CAT) score improved from 23 to 9, and the Modified Medical Research Council (mMRC) dyspnea scale improved from 3 to 2.Conclusion: Eight weeks of pulmonary rehabilitation showed benefits for the patient in reducing dyspnea and improving exercise tolerance and quality of life, especially in hospital-based settings.